Determining the probability of spondyloarthritis in patients with uveitis - A. A. Godzenko; I. Yu. Razumova; S. I. Glukhova (Научно-практическая ревматология, 2024)
Background. Uveitis is a heterogeneous group of inflammatory eye diseases, some of which may be associated with spondyloarthritis (SpA). The probability of SpA depends on the clinical features of uveitis.The aim – to develop a prognostic formula for determining the probability of spondyloarthritis in patients with uveitisMethods. 208 patients (pts) (79 men and 129 women) with different forms of uveitis, referred by ophthalmologists to the V.A. Nasonova Research Institute of Rheumatology, were assessed. The onset of uveitis at the age ≤30 years took place in 107/208 pts (51.44%), over 30 years – in 101 (48.56%). 139/208 pts had acute recurrent uveitis, 69 – chronic; 149 had isolated anterior uveitis (АU), 59 – posterior eye involvement, 160 had unilateral uveitis, 48 – bilateral; HLA-B27 was detected in 159 pts. Various SpA were identified in 60 cases and not confirmed in 148 pts. Groups of pts with and without SpA were compared by gender, age of uveitis onset, presence of HLA-B27, and clinical features of uveitis.Result. SpA was diagnosed in 45/139 pts with acute recurrent uveitis , and was not confirmed in 94/139 (odds ratio (OR) – 1.723; 95% confidence interval (95% CI): 0.879–3.379; p=0.113); SpA was confirmed in 15/69 pts with chronic uveitis, in 54/69 – with other forms of uveitis (OR=0.597; 95% CI: 0.304–1.172; p=0.134). SpA was diagnosed in 51/160 pts with unilateral uveitis and was not diagnosed in 109/160 (OR=2.028; 95% CI: 0.913–4.501; p=0.082); out of 48 pts with bilateral uveitis was 9 with SpA and 39 without SpA (OR=0.493; 95% CI: 0.222–1.095; p=0.082); among 149 pts with isolated AU – 55 with SpA and 94 without SpA (OR=6.319; 95% CI: 2.384–16.749; p=0.001); of 59 pts with panuveitis – 5 with SpA and 54 without SpA (OR=0.158; 95% CI: 0.060–0.419; p=0.001); among 159 HLA-B27-positive – 56 with SpA and 103 without SpA (OR=6.117; 95% CI: 2.091–17.888; p=0.001); the onset of uveitis at the age of ≤30 years was in 44/107 pts with SpA and in 63/107 – without SpA (OR=3.710; 95% CI: 1.921–7.168; p=0.001); SpA was confirmed in 39/79 male pts and was not confirmed in 40 (OR=5.014; 95% CI: 2.637–9.535; p=0.001).A formula to determine the probability of SpA in pts with uveitis was obtained by the method of multifactorial discriminant analysis: 1.972 × Х1 + 1.476 × Х2 + 1.418 × Х3 + 1.270 × Х4 + 0.668 × Х5 + 0.162 × Х6, where X1 – male; X2 – the onset of uveitis at the age of ≤30 years; X3 – HLA-B27; X4 – isolated anterior uveitis; X5 – unilateral uveitis; X6 – acute recurrent uveitis.If the amount is greater than 4.552, the probability of SpA is estimated as high, if the amount is less than or equal to 4.552, it is low.Conclusion. A combination of significant clinical parameters of uveitis (male, onset of uveitis at the age ≤30 years, HLA-B27, isolated anterior uveitis, unilateral lesion, acute recurrent course) allows to quantify the risk of SpA, that contributes to the timely diagnosis.